Production of chlorine-containing functional group doped graphene powders using Yucel's method as anode materials for Li-ion batteries - Gursu, Hurmus; Guner, Yagmur; Arvas, Melih Besir; Dermenci, Kamil Burak; Savaci, Umut; Gencten, Metin; Turan, Servet; Sahin, Yucel (ROYAL SOC CHEMISTRY, 2021)
In this study, the one-step electrochemical preparation of chlorine doped and chlorine-oxygen containing functional group doped graphene-based powders was carried out by Yucel's method, with the resultant materials used as anode materials for lithium (Li)-ion batteries. Cl atoms and ClOx (x = 2, 3 or 4) groups, confirmed by X-ray photoelectron spectroscopy analysis, were covalently doped into the graphene powder network to increase the defect density in the graphene framework and improve the electrochemical performance of Li-ion batteries. The microscopic properties of the Cl-doped graphene powder were investigated by scanning electron microscopy and transmission electron microscopy (TEM) analyses. TEM analysis showed that the one-layer thickness of the graphene was approximately 0.33 nm. Raman spectroscopy analysis was carried out to determine the defect density of the graphene structures. The G peak obtained in the Raman spectra is related to the formation of sp(2) hybridized carbons in the graphene-based powders. The 2D peak seen in the spectra shows that the synthesized graphene-based powders have optically transparent structures. In addition, the number of sp(2) hybridized carbon rings was calculated to be 22, 19, and 38 for the Cl-GP1, Cl-GP2, and Cl-GOP samples, respectively. As a result of the charge/discharge tests of the electrodes as anodes in Li-ion batteries, Cl-GP2 exhibits the best electrochemical performance of 493 mA h g(-1) at a charge/discharge current density of 50 mA g(-1).
Keywords: GRAPHITE NEGATIVE ELECTRODES; ELECTROCHEMICAL EXFOLIATION; POTENTIAL APPLICATION; CYCLIC VOLTAMMETRY; IN-SITU; PERFORMANCE; OXIDE; SUPERCAPACITOR; PHOTOCATALYSIS; NANOSHEETS; Chemistry